Critical-chain project management in Western Australia: Towards construction project duration reduction - Whyte, Andrew; Crew, A. (2011)
Given that one in three infrastructure projects in (Western) Australia were completed over-time, project management of the building process requires re-examination; Critical-Chain Project Management (CCPM) is presented as a way to address unsuccessful, over-time delivery of projects for the local construction industry. CCPM is an application of the Theory of Constraints to establish procedures to better manage human behaviour and more efficiently allocate resources required to complete tasks. CCPM is presented as a means to improve upon the Australian construction industry's more commonly used Critical Path Method. The research work described uses a qualitative methodology to assess the extent to which stakeholders in WA might be able to implement this alternative scheduling technique to incorporate risk assessment. Findings are presented which suggest that whilst industry appears resistant overall to the implementation of CCPM, utilisation of the technique may be suitable for disaster-mitigation community-asset-instatement.